Effect of Different Endodontic Access Cavity Designs in Combination with WaveOne Gold and TruNatomy on the Fracture Resistance of Mandibular First Molars: A Nonlinear Finite Element Analysis - Vorster, Martin; Gravett, Dewald Zane; van der Vyver, Peet J.; Markou, George (My University, 2023)
This study evaluated the effect of traditional and conservative endodontic access cavity designs in combination with WaveOne Gold and TruNatomy instrumentation systems on the fracture resistance of mandibular first molars by means of nonlinear finite element analysis (FEA).
Keywords: Access cavity; TruNatomy; WaveOne Gold; conservative endodontic access; nonlinear finite element analysis; traditional endodontic access